Fluorescent Peptide-PNA Chimeras for Imaging Monoamine Oxidase A mRNA in Neuronal Cells - Sethi, Dalip (2012)
Monoamine oxidases (MAO) catalyze the oxidative deamination of many biogenic amines and are integral proteins found in the mitochondrial outer membrane. Changes in MAO-A levels are associated with depression, trait aggression and addiction. Here we report the synthesis, characterization and in-vitro evaluation of novel fluorescent peptide-peptide nucleic acid (PNA) chimeras for MAOA mRNA imaging in live neuronal cells. The probes were designed to include MAOA-specific PNA dodecamers, separated by an N-terminal spacer to a μ-opioid receptor targeting peptide (DAMGO), with a spacer and a fluorophore on the C-terminus. The probe was successfully delivered into human SH-SY5Y neuroblastoma cells through μ-opioid receptor-mediated endocytosis. The K(d) by flow cytometry was 11.6 ± 0.8 nM. Uptake studies by fluorescence microscopy showed ~5-fold higher signal in human SH-SY5Y neuroblastoma cells than in negative control CHO-K1 cells that lack μ-opioid receptors. Moreover, a peptide-mismatch control sequence showed no significant uptake in SH-SY5Y cells. Such mRNA imaging agents with near infrared fluorophores might enable real time imaging and quantitation of neuronal mRNAs in live animal models.